High-Dose Dependence and Cognitive Side Effects to Medical Prescription of Etizolam - Tamburin, Stefano; Mantovani, Elisa; Bertoldi, Anna; Federico, Angela; Casari, Rebecca; Lugoboni, Fabio (Frontiers in Psychiatry, 2020)
Introduction. The use of novel designer drugs has increased worldwide over the years. Etizolam is a designer benzodiazepine (BZD) that has raised concern because of its growing non-medical use, liability to tolerance and dependence, and related harms. Studies exploring the abuse liability and cognitive effects of etizolam outside the therapeutic doses are lacking. Aims. To explore the abuse liability of etizolam and the characteristics of patients affected by etizolam high-dose dependence in a nationwide tertiary referral addiction unit. To document the cognitive changes to etizolam high-dose use. Design and methods. Sociodemographic and clinical data on subjects with etizolam high-dose use were retrospectively collected from a database of 1293 patients consecutively admitted to the Addiction Medicine Unit, Verona University Hospital, Italy for detoxification from high-dose BZDs or Z-drugs dependence. Thorough neuropsychological testing explored the cognitive side effects of high-dose etizolam use. Results. We found eleven etizolam high-dose users, of which eight used etizolam only, and three used etizolam with other BZDs/zolpidem. All the patients were prescribed etizolam for medical reasons, i.e., anxiety and/or insomnia. Neuropsychological evaluation showed deficits of working memory, visuospatial memory and executive function in a 27-year-old woman who used etizolam 15 mg daily. Discussion. Our findings suggest that abuse and dependence liability of etizolam should be considered a public health and social problem. They offer preliminary evidence on the cognitive side effects of etizolam high-dose use. Conclusions. This report offers new information on the potential harms of etizolam in patients who are prescribed this drug for medical reasons.